Techniques improving electrical cardioversion success for patients with atrial fibrillation: a systematic review and meta-analysis. Issue 2 (12th December 2022) - Nguyen, Stephanie T; Belley-Côté, Emilie P; Ibrahim, Omar; Um, Kevin J; Lengyel, Alexandra; Adli, Taranah; Qiu, Yuan; Wong, Michael; Sibilio, Serena; Benz, Alexander P; Wolf, Alex; Whitlock, Nicola J; et al.
Abstract: Aims: Electrical cardioversion is commonly used to restore sinus rhythm in patients with atrial fibrillation (AF), but procedural technique and clinical success vary. We sought to identify techniques associated with electrical cardioversion success for AF patients. Methods and results: We searched MEDLINE, EMBASE, CENTRAL, and the grey literature from inception to October 2022. We abstracted data on initial and cumulative cardioversion success. We pooled data using random-effects models. From 15 207 citations, we identified 45 randomized trials and 16 observational studies. In randomized trials, biphasic when compared with monophasic waveforms resulted in higher rates of initial [16 trials, risk ratio (RR) 1.71, 95% CI 1.29–2.28] and cumulative success (18 trials, RR 1.10, 95% CI 1.04–1.16). Fixed, high-energy (≥200 J) shocks when compared with escalating energy resulted in a higher rate of initial success (four trials, RR 1.62, 95% CI 1.33–1.98). Manual pressure when compared with no pressure resulted in higher rates of initial (two trials, RR 2.19, 95% CI 1.21–3.95) and cumulative success (two trials, RR 1.19, 95% CI 1.06–1.34). Cardioversion success did not differ significantly for other interventions, including: antero-apical/lateral vs. antero-posterior positioned pads (initial: 11 trials, RR 1.16, 95% CI 0.97–1.39; cumulative: 14 trials, RR 1.01, 95% CI 0.96–1.06); rectilinear/pulsed biphasic vs. biphasic truncated exponential waveform (initial: four trials, RR 1.11, 95% CI 0.91–1.34; cumulative: four trials, RR 0.98, 95% CI 0.89–1.08) and cathodal vs. anodal configuration (cumulative: two trials, RR 0.99, 95% CI 0.92–1.07). Conclusions: Biphasic waveforms, high-energy shocks, and manual pressure increase the success of electrical cardioversion for AF. Other interventions, especially pad positioning, require further study. Graphical Abstract: Graphical Abstract